Socio-economic design of control charts for monitoring service processes: a case study of a restaurant system. Issue 6 (2nd November 2019) - Ebadi, Mohsen; Ahmadi-Javid, Amir
ABSTRACT: The main purpose of this paper is to design a control chart for monitoring the service processes in congested immobile single-stage service systems where customer arrivals are time dependent. It is investigated how social and economic/statistical aspects of the control chart can be addressed. As customer satisfaction is a key success factor for a service system, our proposed design method incorporates cost minimization and service quality maximization as two conflicting objective functions to constitute a bi-objective optimization model. The service quality is measured by the waiting time required to obtain a service, and a constraint is considered to guarantee the statistical performance of the control chart. Simulation-based optimization is used to obtain Pareto-optimal designs. A case study of a local restaurant is presented where the daily customers' data are used to estimate the required parameters. The results show that the proposed method is able to make a trade-off between the quality-control cost and the customer waiting time. They also indicate how the resulting design is sensitive to the misspecification of the input parameters.